An early innate response underlies severe influenza‐induced exacerbations of asthma in a novel steroid‐insensitive and anti‐IL‐5‐responsive mouse model. Issue 5 (10th November 2016) - Ravanetti, L.; Dijkhuis, A.; Sabogal Pineros, Y. S.; Bal, S. M.; Dierdorp, B. S.; Dekker, T.; Logiantara, A.; Adcock, I. M.; Rao, N. L.; Boon, L.; Villetti, G.; Sterk, P. J.; et al.
Abstract: Background: Acute worsening of asthma symptoms (exacerbation) is predominantly triggered by respiratory viruses, with influenza causing the most severe exacerbations. The lack of an adequate animal model hampers mechanistic insight and the development of new therapeutics. Aim: We developed and characterized a robust, consistent, and reproducible mouse model of severe exacerbation of chronic allergic asthma. Methods: Chronic allergic airway inflammation was induced following a house dust mite (HDM) sensitization protocol. HDM‐sensitized mice and controls were infected with influenza virus A/X31 H3N2 and either or not treated with inhaled fluticasone propionate (FP), systemic corticosteroids (Pred), or anti‐IL‐5. Mice were killed at different time points after infection: Cellular accumulation and cytokines levels in the airways, PenH as a measure of airway hyper‐responsiveness (AHR), and lung histology and viral replication were assessed. Results: Infection with low‐dose A/X31 H3N2 led to prolonged deterioration of lung function, aggravated mucus production, peri‐vascular, peri‐bronchial, and allergic inflammation that was unresponsive to inhaled corticosteroids, but responsive to systemic corticosteroids. The exacerbation was preceded at 14 h after virus exposure by a marked innate, but no Th2 and Th1 response subsequently followed by enhanced numbers of eosinophils, neutrophils, dendritic, and T cells into the lung lumen, parenchyma, and draining lymph nodes in HDM‐sensitized mice. Anti‐IL‐5 treatment attenuated eosinophils and prevented the X31‐induced exacerbation. Conclusions: Together, these findings indicate that an early innate response that involves eosinophils underlies the exacerbation. This model recapitulates all major features of severe asthma exacerbations and can serve to discern driving mechanisms and promote the development of novel therapeutics.